Microbial community dynamics in two Central European peatlands affected by different nitrogen depositions - Barta, Jiri; Santruckova, Hana; Novak, Martin; Cejkova, Bohuslava; Jackova, Ivana; Buzek, Frantisek; Stepanova, Marketa; Curik, Jan; Veselovsky, Frantisek; Prechova, Eva (FEMS microbiology ecology, 2025)
Changes in organic matter accumulation in wetlands are critical for climate dynamics. Different nitrogen (N) inputs in Sphagnum-dominated peat bogs can lead to varying rates of carbon (C) and N accumulation, influencing greenhouse gas emissions. We investigated how contrasting N deposition shapes microbial communities in two Czech peat bogs, focusing on biological N2 fixation (BNF) as a key N input in pristine wetlands. Higher N deposition resulted in a more active microbial community with increased enzyme activity and C acquisition, potentially accelerating decomposition and reducing C storage. Enhanced denitrification, indicated by active nosZ Clade I genes, suggests that higher N inputs may increase N losses through denitrification. In contrast, the lower N site showed a less active microbial community with slower decomposition, beneficial for C sequestration, though potentially less adaptable to future N increases. Experimental BNF rates were 70 times higher at the high N site, consistent with elevated diazotroph activity indicated by active nifH gene. Phosphorus (P) availability and NH4+/NO3- ratios appeared to drive BNF differences, emphasizing the need for managed N inputs to maintain peatland ecological functions.
Keywords: Sphagnopsida; Sphagnum; mokřady; fosfor; Denitrification; Nitrogen; mikrobiota; Česká republika; nitrogen deposition; uhlík; Bacteria; denitrification; Wetlands; Soil Microbiology; Microbiota; denitrifikace; Soil; rašeliníky; Czech Republic; Nitrogen Fixation; Carbon; dusík; fixace dusíku; microbiome; půdní mikrobiologie; biological nitrogen fixation; půda; Phosphorus; peat bog